Extensive ribosomal DNA amplification during Andean common bean (Phaseolus vulgaris L.) evolution - Pedrosa Harand, Andrea; Souza Almeida, C.C. de; Mosiolek, M; Blair, Matthew W.; Schweizer, D.; Guerra, M. (Springer, 2006)
The extent of 5S and 45S ribosomal DNA (rDNA) variation was investigated in wild and domesticated common beans (Phaseolus vulgaris) chosen to represent the known genetic diversity of the species. 5S and 45S rDNA probes were localized on mitotic chromosomes of 37 accessions by fluorescent in situ hybridization (FISH). The two 5S rDNA loci were largely conserved within the species, whereas a high variation in the number of 45S rDNA loci and changes in position of loci and number of repeats per locus were observed. Domesticated accessions from the Mesoamerican gene pool frequently had three 45S rDNA loci per haploid genome, and rarely four. Domesticated accessions from Andean gene pool, particularly from the race Peru, showed six, seven, eight or nine loci, but seven loci were found in all three races of this gene pool. Between three and eight loci were observed in accessions resulting from crosses between Andean and Mesoamerican genotypes. The presence of two to eight 45S rDNA loci in wild common beans from different geographic locations indicates that the 45S rDNA amplification observed in the Andean lineage took place before domestication. Our data suggest that ectopic recombination between terminal chromosomal regions might be the mechanism responsible for this variation.